Theoretical investigation on the mechanism and kinetics of the ring-opening polymerization of ε-caprolactone initiated by tin(II) alkoxides - Chanchai Sattayanon (2018)
A theoretical investigation of the ring-opening polymerization (ROP) mechanism of ε-caprolactone (CL) with tin(II) alkoxide, Sn(OR) 2 initiators (R = n-C 4 H 9 , i-C 4 H 9 , t-C 4 H 9 , n-C 6 H 13 , n-C 8 H 17 ) was studied. The density functional theory at B3LYP level was used to perform the modeled reactions. A coordination-insertion mechanism was found to occur via two transition states. Starting with a coordination of CL onto tin center led to a nucleophilic addition of the carbonyl group of CL, followed by the exchange of alkoxide ligand. The CL ring opening was completed through classical acyl-oxygen bond cleavage. The reaction barrier heights of ε-caprolactone with different initiators were calculated using potential energy profiles. The reaction of ε-caprolactone with Sn(OR) 2 having R = n-C 4 H 9 has the least value of barrier height compared to other reactions. The rate constants for each reaction were calculated using the transition state theory with TheRATE program. The rate constants are in good agreement with available experimental data. © 2013 Springer-Verlag Berlin Heidelberg.